Handbook of Autism and Pervasive Developmental Disorders - Cohen, Donald J.; Donnellan, Anne M.; Paul, Rhea (Winston ; Wiley, 1987)
Keywords: Autism; Developmental disabilities; Autistic children; Services for; Services for; Developmentally disabled children; dept.cmd; faculty_collection

Contemporary Approaches in Stuttering Therapy - Peins, Maryann (Little, Brown, 1984)
Keywords: Stuttering; Treatment; Speech therapy; Treatment; Stuttering in children; dept.cmd; faculty_collection

Frequency and duration effects on perceptions of rise-time rate - Sansone Jr., F.E. (IRCS Medical Science, 1983)
The ability to accurately perceive the acoustic correlate of glottal attack, phonatory onset rise-time rate, can be diagnostically critical for speech pathologists conducting voice function examinations. Signal onset duration may serve as a cue in these perceptions because an inverse relationship exists between onset duration and rise-time rate. Other acoustic information such as frequency, present during voice initiation, might also affect phonatory onset rise-time perceptions. This study was designed to determine if listeners can detect duration related rise-time rate differences in the presence of variable frequency. Listeners accurately detected rise-time rates associated with onset duration differences independent of the frequency variable. A significant duration effect was revealed with no frequency or variable interaction effects. All judgement means were significantly different from one another. It was determined that as stimulus onset duration decreased, onset rise-time rate was perceived to occur more rapidly.
Keywords: auditory discrimination; auditory system; dept.cmd; hearing; human; human experiment; normal human; phonation; speech; ⛔ No DOI found

Effects of electronic voice intensity monitoring on hard glottal attack - Sansone Jr., F.E. (IRCS Medical Science, 1982)
An electronic device capable of monitoring the rate at which voice intensity increases during voice onset provides an indicator of the abruptness of phonatory initiation. Two groups of 8 subjects were taught to reduce the abruptness of glottal attack. Group A used a seven step program employing the electronic monitor while Group B used the same seven step program but with a traditional approach to the reduction of abrupt glottal attack substituted for monitor use. Both groups used a self-instruct teaching paradigm. Subject recordings of pre and post program production of five voice onset moments were submitted to sonographic amplitude analysis and a time/intensity slope ratio was calculated for each. Further, the pre and post program recordings were judged for abruptness of glottal attack. Post program slope ratios and attack judgments were significantly different (p < 0.01) from pre program data for Group A only. These data suggest that electronic monitoring was effective in producing gradual phonatory initiation.
Keywords: central nervous system; dept.cmd; glottis spasm; human cell; larynx; normal human; phonation; voice; ⛔ No DOI found

Perceived utility of a self-evaluation procedure by students in speech-language pathology - Mercaitis, Patricia A; Wener, Deena L (The Clinical Supervisor, 1988)
A 58-item Likert attitude scale was developed and administered to thirty Speech-Language Pathology graduate students in order to obtain their perceptions of a self-evaluation procedure used in a clinical training facility. Significant correlations were obtained between the clinicians’ perception of the overall usefulness of this self-evaluation procedure, and a majority (61%) of the items on the scale. Significant correlations were obtained for several pairs of demographic items. The implications of these results for the clinical supervision process are discussed, as well as the need for further research on this topic. © 1988 by The Haworth Press, Inc. All rights reserved.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-646-942-990-571 tex.type: [object Object]
Keywords: dept.cmd

Speech considerations in prosthodontic rehabilitation of the glossectomy patient - Mckinstry, Robert E; Aramany, Mohamed A; Beery, Quinter C; Sansone, Frank (Journal of Prosthetic Dentistry, 1985)
A knowledge of normal articulation is needed before the prosthodontist can assess the compensatory articulation used by glossectomy patients. The amount and portion of tongue resected is directly correlated with speech intelligibility. The loss of the tip of the tongue is more critical to intelligibility than a hemiglossectomy. Partial glossectomy speakers can often use the residual tongue stump to perform adaptive movements that approximate normal movements and should be treated as an articulation problem. The compensatory articulation used by the total glossectomy patient was reviewed. The prosthodontic management of patients with partial tongue resection often includes lowering the palatal vault, while the management of the total glossectomy patient usually requires a mandibular tongue prosthesis. These prostheses can be refined with the use of multiview videofluoroscopy, videotaping, and spectrographic analysis. © 1985.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/058-110-990-398-611 tex.type: [object Object]
Keywords: Dentures; Glossectomy; Human; Mandible; Prostheses and Implants; Prosthesis Design; Speech Articulation Tests; Speech Disorders; Tongue; article; denture; dept.cmd; glossectomy; human; mandible; prostheses and orthoses; prosthesis; speech analysis; speech disorder; tongue

Instrumentation for monitoring lingual pressure in vibrotactile research - Kingsbury, Gary D; Sansone, E Frank; Kelly, Dan H (Review of Scientific Instruments, 1984)
In order to avoid obtaining variable measurement data it is critical to control pressure applied to the tongue by positioning clamps used in lingual vibrotactile research. A pressure sensing plate, associated electronics, and procedures are described which, when employed with positioning clamps in current use, will permit monitoring lingual pressure during vibrotactile investigations.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/114-981-553-013-894 tex.type: [object Object]
Keywords: dept.cmd

A comparison of the intelligibility of esophageal, electrolaryngeal, and normal speech in quiet and in noise. - Holley, Sandra Cavanaugh; Lerman, Jay W; Randolph, Kenneth (Journal of Communication Disorders, 1983)
The effect of different levels of a multiple-talker background noise on the intelligibility of normal, esophageal, and electrolaryngeal speech was investigated. A superior laryngectomized male speaker and a normal-age matched male speaker produced the speech stimuli used in the study. Audiotape recordings of the speakers were presented to panels of naive listeners. The data from the listeners' responses revealed significant differences in the intelligibility of normal, esophageal, and electrolaryngeal speech as a function of the background noise level. The data did not indicate a superiority of one form of alaryngeal speech over the other in adverse noise conditions. © 1983.
23 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1983QY97400007, lens.org/077-212-672-431-70X tex.type: [object Object]
Keywords: Adolescent; Adult; Comparative Study; Female; Human; Male; Noise; Phonetics; Speech Intelligibility; Speech; Alaryngeal; Speech; Esophageal; adolescent; adult; article; comparative study; dept.cmd; esophagus speech; female; human; male; methodology; noise; phonetics; speech intelligibility

Clinical estimation of fundamental frequency: The 3m plastiform magnetic tape viewer - Kelly, Dan H; Sansone, Frank (Journal of Communication Disorders, 1981)
A procedure and method is described to determine the frequency or pitch of tape-recorded voice samples, while keeping the cost of measurement within the reach of practicing clinicians. The method described reduces the uncertainty of pitch determination by comparison techniques and improves the accuracy of clinical estimation of fundamental vocal frequency and pitch. The accuracy, reliability, cost, and ease with which the method can be used makes it a viable tool to be used by the clinician. © 1981.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-059-031-584-761 tex.type: [object Object]
Keywords: Human; Methods; Pitch Perception; Tape Recording; Voice Disorders; article; dept.cmd; hearing; human; instrumentation; larynx disorder; tape recorder; technique